A study of the publication exchange program of selected academic libraries in Metro Manila problems and issues - Garvilles, Jesserylle G.; Lapuz, Elvira B. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2005)
This study was conducted to examine the existing publication exchange program among selected academic libraries in Metro Manila and to determine the problems and issues encountered by the librarians in the processes and procedures of exchanges. To do this, the factors that affect the publication exchange program were closely analyzed - sources of funds, the qualities of institutions' publications send and received, and the support it have from the university and college administration.
This study utilized a descriptive survey method of inquiry. Survey questionnaires were handed out to the librarian in-charge of the gifts and exchange section and to other library personnel of the eleven libraries studied. Interviews were also conducted.
Findings revealed that library budget, number of skilled staff, heterogeneity and relevance of the institutions' publication, transmission of exchange materials and administrative support affect the efficiency of exchange of scholarly materials among academic libraries.
Recommendations include the provision of an adequate library budget, formalization and formulation of written publication exchange policies, a separate section and a person who solely handles gifts and exchange and an up-to-date exchange lists. It is also recommended that the academic libraries should endeavor to find partner in neighboring academic and research institution in the locality and be geared towards the needs of the institution. Also, to government subsidized academic institutions, it is recommended that the libraries should participate in resource sharing and other inter-library cooperation to further improve their collection.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Exchanges, literary and scientific -- Philippines -- Manila Metropolitan Area; Academic libraries -- Philippines -- Manila Metropolitan Area